New insights into the electrochemical behaviour of porous carbon electrodes for supercapacitors. (October 2018) - Ibrahim Abouelamaiem, Dina; Mostazo-López, María José; He, Guanjie; Patel, Drasti; Neville, Tobias P.; Parkin, Ivan P.; Lozano-Castelló, Dolores; Morallón, Emilia; Cazorla-Amorós, Diego; Jorge, Ana Belen; Wang, Rongfang; Ji, Shan; et al.
Graphical abstract: Highlights: In situ Raman is coupled with electrochemistry to detect carbon structure. Surface science and porous texture dictate supercapacitor performance at extreme potentials. Hydrogen and oxygen evolution can be delayed in porous carbon electrodes. Energy delivery can be enhanced with optimizing pore size and oxygen content. Abstract: Activated carbons, with different surface chemistry and porous textures, were used to study the mechanism of electrochemical hydrogen and oxygen evolution in supercapacitor devices. Cellulose precursor materials were activated with different potassium hydroxide (KOH) ratios, and the electrochemical behaviour was studied in 6 M KOH electrolyte. In situ Raman spectra were collected to obtain the structural changes of the activated carbons under severe electrochemical oxidation and reduction conditions, and the obtained data were correlated to the cyclic voltammograms obtained at high anodic and cathodic potentials. Carbon-hydrogen bonds were detected for the materials activated at high KOH ratios, which form reversibly under cathodic conditions. The influence of the specific surface area, narrow microporosity and functional groups in the carbon electrodes on their chemical stability and hydrogen capture mechanism in supercapacitor applications has been revealed.